The role of International Monetary Fund in Planning monetary policy for Developing the Iraqi economy: An Applied Research for the Period (2004-2013) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The developing countries, like our country Iraq suffer from deep comprehensive structural crisis, manifestations and a clear imbalance between the demand and the supply sides. The overall imbalance in the external balance. As a consequence, this caused the accumulation of foreign debts or failure in the implementation of economic development programs. The countries which are forced to resort to the International Monitoring Funds, and the World Bank for assistance and to express an opinion on policies that include restrictions controls that belong to the monetary, and fiscal side group, imposed on the economies crisis, as a condition for returning to normal which called reform programs. The organize of the events of radical changes in the economic structure towards the rule of the free market system trends in the domestic and international economic activity, carried out by the top financial institutions in the country like the Central Bank, for example, in order to improve the complete level of demand commensurate, with the full level of supply and return to the state of economic balance. The structural adjustment programs, that represents the advanced phase of the restoration of capitalism in which direct changes in agreement with those of international institutions, and under strict supervision conducted restructuring process. The structural adjustment policies programs, or called the government programs, as a prelude to conclude agreements on debt rescheduling, or as a kind of show good intentions and behavior begins her request.The standard requirements for the procedures of the International Monetary Fund, including application procedures for government authorities for tax, and financial sector reform, restructuring state-owned enterprises, and macroeconomic stability.